THE SETTLEMENT OF THE DISPUTE OF “COLLECTIVE” VIOLENCE BY THE POLICE - M. Yusran (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
Indonesia Republic State Police is a tool that plays a role in maintaining state security and public order, enforce the law and provide protection, guidance, and service to the community within the framework of maintaining internal security “. According to Police Act Number 2 of Year 2002 in Article 18 explained that the police were given the authority under certain circumstances to do according to his own judgment or be known as a functional discretionary powers which puts persons of police as a central factor in law enforcement. Discretion is the authority of the police to make a decision or choose different actions in resolving issues of law or violation of criminal cases are handled. Police discretion is an authority given to the police, to make decisions in certain situations that require separate consideration and involves moral issues and lies within the boundary line between the legal and the moral. One of the scope of police discretion is collective violence. Collective violence is violence committed by a group of people who performed together , this collective violence associated with irrationality, emotionality and impersonation individuals who escape the social restrictions of a social organization. Individuals who are in a group / crowd considered mimic each other, so that mutually reinforce and enlarge emotionality and irrationality of others Keywords : Policing , Discretion , Collective Violence